Bhutan : Private Sector Survey - World Bank (Washington, DC, 2013)
Two of the seven major development challenges of the Royal Government of Bhutan identified for the Donors Development Forum, held in Thimpu in November 2000, were private sector development and employment generation. Given the fact that the public sector is unlikely to expand further in the forseeable future, these issues become two sides of the same coin. Future employment generation in Bhutan can only come from the further growth of the private sector. The prinicpal objectives of this report and associated survey work is to assist the Government in developing an improved information base on the private sector and to thereby assist it in formulating its strategy for private sector support over the period of the Ninth Five-Year Development Plan. The main recommendations put forth for private sector development include: Establishment of a transparent system of tax relief and possibly a system of industry levies to support radically increased worker and management training. Development of a transparent, time-bound, policy for recruiting non-national workers. Encouragement of the development of innovative financial instruments and payment modalities. Support of technology transfer mechanisms and provide incentives through tax breaks. Finalization and approval of the new foreign direct investment law. Implementation of a system of duty drawback on imported raw materials used to produce export products. Development of a clear, consistent, and transparent policy environment.